Tafsir Islami atas Perjuangan Sultan Khairun dalam Melawan Portugis di Kawasan Maluku Utara (Sebuah Analisis Berdasarkan Teori Islam dan Teori Politik Kolonial Niccolo Machiavelli) - Darmawijaya Darmawijaya (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
This article is a study of Ternate history by using the religious per-spective as a tool in order to present a historical study of the relationship between the Sultanate of Ternate and the Portuguese. This study indicates that Sultan Khairun is a good, sincere, intellect and caring Sultan in maintaining relationships with the Portuguese in Ternate which came to the island before he was appointed as Sultan. In an effort to maintain a good relationship with the Portuguese, Sultan tried to promote respect for guests, forgiving, honest and keep promises, and assume good faith (positive thinking). It can be seen, for example, from the attitude of the Sultan Khairun when giving Francis Xavier an in-depth discussion and efforts to forgive two Portuguese governors who had detained and arrested him unilaterally. He also accepted the invitation from Lopes de Masquita to hold a peace agreement. Though the peace talk was just a cunning strategy of the Portuguese Governor to paralyze the Sultan Khairun. As a consequence, Sultan Khairun was killed at Fort Kastela. His death is martyrdom in the way of Allah in order to build a good relationship consistently for the betterment of his country. It is all a reflection of a Sultan who was inspired by the teachings of Islam to build a safe, fair and prosperous civilization. Key Words : Islamic exegesis, Sultan Khairun, and Portuguese. Artikel ini merupakan kajian sejarah Ternate dengan menggunakan ilmu agama sebagai alat bantu dalam rangka menghadirkan sebuah kajian sejarah hubungan antara Kesultanan Ternate dan Portugis. Studi ini mengindikasikan bahwa Sultan Khairun adalah seorang Sultan yang baik, intelek ikhlas dan berlapang hati dalam menjaga relasinya dengan Portugis yang telah ada di Ternate sebelum ia diangkat sebagai Sultan. Dalam upaya menjaga relasinya dengan Portugis, Sultan berusaha mengedepankan sikap menghargai tamu, pemaaf, jujur dan menepati janji, serta berprasangka baik (berpikir positif). Itu bisa terlihat, misalnya, dari sikap Sultan Khairun yang berusaha melayani Francis Xavier dalam berdiskusi secara mendalam dan usahanya dalam memaafkan dua Gubernur Portugis yang telah menahan dan menangkapnya secara sepihak. Sikapnya yang baik itu terlihat kembali ketika ia menerima dengan baik ajakan Lopes de Masquita untuk mengadakan perjanjian damai. Padahal perjanjjian damai itu hanyalah strategi licik dari Sang Gubernur untuk melumpuhkan Sultan Khairun. Melalui tipuan licik itu, Sultan Khairun yang baik dan intelek itu harus rela menemui kematian secara mengenaskan di Benteng Kastela. Kematiannya merupakan kematian syahid di jalan Allah dalam rangka membangun hubungan yang baik secara konsisten demi kemajuan negerinya. Itu semua adalah cerminan seorang Sultan yang banyak diilhami oleh ajaran Islam yang ingin membangun peradaban yang aman, adil dan makmur. Kata Kunci : Tafsir Islami, Sultan Khairun dan Portugis.